IOT-Driven Smart Energy Monitoring: Development of Simonde in Telecommunication Laboratory - Ade Irfansyah; Yuyun Suprapto; Nyaris Pambudiyatno; Bambang Bagus Hariyanto; Teguh Imam Suharto (Universitas Negeri Malang, 2025)
Accurate electrical energy monitoring is essential for effectively managing its usage. The Internet of Things (IoT) technology offers an optimal solution for real-time monitoring. This study aims to design and implement an IoT-based Power and Energy Monitoring System (SiMONDE) that efficiently monitors electrical energy usage in a telecommunications laboratory in real-time. The research employs a research and development methodology with the ADDIE model approach, encompassing three phases: (1) analysis, (2) design, and (3) development. The results indicate significant errors in SiMONDE when measuring current in the range of 0.3 to 0.12 Amperes, compared to a clamp meter. However, when measuring currents between 1.6 and 3.7 Amperes, SiMONDE exhibits a low error margin. Additionally, SiMONDE's media feasibility and usage feasibility percentages are 97.5% and 96.87%, respectively. The study concludes that SiMONDE is not sufficiently accurate for low-current measurements, yet demonstrates high usability feasibility according to user needs.